Prognosis of Surgical Management for Intracerebral Hemorrhage: Insights from Indonesia's National Brain Center Hospital - Rahmatisa, Dimas; Lasanudin, Joshua Eldad Frederich (Jurnal Neuroanestesi Indonesia, 2024)
Background and Objective: Intracerebral hemorrhage (ICH), a stroke subtype that can be managed surgically, exhibits varying prognoses amongst countries. However, data for the Indonesian population are currently lacking. Subject and Methods: In a retrospective cohort study, medical records of post-surgical ICH cases in Rumah Sakit Pusat Otak Nasional from January 2021 to April 2023 were obtained. Prognostic data includes hospitalization duration, in-hospital mortality, and dependency upon discharge. Multivariate analysis was performed on sociodemographic and medical data to determine prognostic factors.Results: A total of 157 cases were obtained. Procedures performed include hemorrhage evacuation craniotomies (58.6%), burr holes (29.9%), ventriculoperitoneal shunts (24.2%), and decompressive craniectomies (5,1%), with 15.9% patients undergoing multiple surgical sessions. In-hospital mortality and total dependency occurred in 31.2% and 54.6% of patients, respectively. Average hospitalization is 16.32 days. Predictors for in-hospital mortality are age ? 50 years (p=0.002), male (p=0.014), hematoma volume 40mL (p=0.012), multiple surgical sessions (p=0.034), and presenting Glasgow Coma Scale (GCS) 9 (p=0.015). Predictors for total dependency are supratentorial lesions (p=0.025) and presenting GCS 9-12 (p=0.008) and 9 (p=0.002). Predictors for hospitalization 2 weeks are stroke onset 3.5 hours (p=0.008) and multiple surgical sessions (p=0.001). Conclusion: Surgical management of ICH in Indonesia reveals similar outcomes to other countries. However, differences in prognostic factors indicate potential variations between countries.